2016
DOI: 10.1159/000443442
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Mitochondrial DNA Level is a Prognostic Marker in Peritoneal Dialysis Patients

Abstract: Background/Aims: Circulating bacterial DNA fragment is related to systemic inflammatory state in peritoneal dialysis (PD) patients. We hypothesize that circulating mitochondrial DNA, which has a similar structure with bacterial DNA, correlates with systemic inflammatory state and predicts cardiovascular event in new PD patients. Methods: We measured plasma mitochondrial DNA level by quantitative polymerase chain reaction (PCR) in 197 new PD patients and 150 patients with chronic kidney disease. PD patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…It should be noted, however, that our local policy mandates hospital admission for many intervention procedures, such as cardiac catheterization and colonoscopy. Unfortunately, we do not have the detailed breakdown on the cause of hospitalization for our patients, but the gure in this study is similar to our previous reports [29,30].…”
Section: Discussionsupporting
confidence: 79%
“…It should be noted, however, that our local policy mandates hospital admission for many intervention procedures, such as cardiac catheterization and colonoscopy. Unfortunately, we do not have the detailed breakdown on the cause of hospitalization for our patients, but the gure in this study is similar to our previous reports [29,30].…”
Section: Discussionsupporting
confidence: 79%
“…The second study indicates that an increased circulating free-mtDNA content (which might be different from cell-derived mtDNA content) correlates with a systemic inflammatory state and is a strong predictor of cardiovascular events. 22 We observed a highly significant and linear inverse relationship between mtDNA copy number and prevalent CVD, which was attenuated but remained significant with additional adjustment for kidney function and CVD risk factors (Table 2). Interestingly, we did not observe a significant association with cardiovascular deaths during the 4 years of follow-up.…”
Section: Cardiovascular Diseasementioning
confidence: 78%
“…[40][41][42] Studies in various patients indeed revealed a higher cell-free mtDNA copy number in patients with clinical outcomes. 22,43,44 Strengths and limitations of the study To our knowledge, this is largest reported study of mtDNA copy numbers in CKD patients using prespecified and centrally adjudicated outcome measures. Moreover, it is the first study demonstrating a strong association between mtDNA copy numbers and risk of mortality and infections in patients with moderately severe CKD.…”
Section: Oxidative Stress As a Possible Explanation Of The Findingsmentioning
confidence: 99%
“…From 1997 to 2008 the number of PD patients increased in developing countries more than in developed countries, and in 2008, 11% of the global dialysis population was performing PD [2-4]. Several studies showed an initial survival benefit of PD in the first 2 years compared to hemodialysis [2, 5, 6], and very recent data from the European Renal Association - European Dialysis and Transplant Association (ERA-EDTA) showed that patient survival has improved over the last 20 years for both PD and hemodialysis (HD) [7].…”
Section: Introductionmentioning
confidence: 99%